2015
DOI: 10.1121/1.4934268
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative acoustic analysis of the vocal repertoire of the common marmoset (Callithrix jacchus)

Abstract: The common marmoset (Callithrix jacchus), a highly vocal New World primate species, has emerged in recent years as a promising animal model for studying brain mechanisms underlying perception, vocal production, and cognition. The present study provides a quantitative acoustic analysis of a large number of vocalizations produced by marmosets in a social environment within a captive colony. Previous classifications of the marmoset vocal repertoire were mostly based on qualitative observations. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(197 citation statements)
references
References 43 publications
3
179
1
2
Order By: Relevance
“…The present study took advantages of behavioral and neural recording techniques that we have pioneered in the past two decades to study behavioral and neurophysiological mechanisms underlying perception, production, and vocal communication in marmosets, as well as the extensive knowledge that we have accumulated on the marmoset's vocal repertoire and behaviors (Miller and Wang, 2006;Pistorio et al, 2006;DiMattina and Wang, 2006;Roy et al, 2011;Agamaite et al, 2015). The animals used in this study were born and raised in a breeding colony that we have maintained at Johns University School of Medicine since 1996.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study took advantages of behavioral and neural recording techniques that we have pioneered in the past two decades to study behavioral and neurophysiological mechanisms underlying perception, production, and vocal communication in marmosets, as well as the extensive knowledge that we have accumulated on the marmoset's vocal repertoire and behaviors (Miller and Wang, 2006;Pistorio et al, 2006;DiMattina and Wang, 2006;Roy et al, 2011;Agamaite et al, 2015). The animals used in this study were born and raised in a breeding colony that we have maintained at Johns University School of Medicine since 1996.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in the playback condition, prerecorded phee calls from other marmosets in our colony were used to evaluate a neuron's sensory responses. Although the acoustics of these phee calls are quantitatively different from those of the experimental subject (Miller et al, 2010b;Miller and Wren Thomas, 2012;Agamaite et al, 2015), there has been no evidence to indicate that listening to an animal's own vocalization evokes significantly different neural responses than those evoked by other marmosets' vocalizations in auditory or frontal cortex other than the differences caused by the acoustics. In some other animal species, such as songbirds, playback of the animal's own songs evokes markedly different neural responses than those evoked by other animals' songs (Margoliash and Konishi, 1985).…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…BFs of HTNs fall well within marmosets' hearing range. Marmosets have a rich vocalization repertoire that contains a variety of harmonic structures (33,43,44). Their vocalizations contain harmonic sounds with both high-frequency f 0 values (>2-3 kHz; e.g., "phee" and "twitter" calls) and low-frequency f 0 values (<2 kHz; covering the range of pitch; e.g., the "egg" calls, "moans," and "squeals" calls).…”
Section: Discussionmentioning
confidence: 99%
“…The marmoset is a highly vocal New World primate, and its vocal repertoire contains rich harmonic structures (33). It has recently been shown that marmosets…”
mentioning
confidence: 99%